The Incidence of EU Per-Hectare Payments on Farmland Rental Rates: A Spatial Econometric Analysis for German Farm-Level Data - Gunnar Breustedt; Hendrik Habermann (Verein für Socialpolitik, 2010)
This article analyses determinants for 2001 farmland rental prices from 3,819 farms in Germany. Based on specification tests we estimate a general spatial model to account for both spatial relationships among rental prices of neighbouring farmers and spatially autocorrelated error terms. Depending on the choice of instrumental variables, a exteuro1 per hectare higher rental price in a farmer's neighbourhood coincides with a exteuro0.64 to exteuro0.74 higher rental price the farmer pays. The marginal incidence of EU per-hectare payments paid for eligible arable crop acreage amounts to exteuro0.48 to exteuro0.95 for each additional exteuro of premium payments. Regional livestock density, which is indirectly influenced by different policies, is also a major determinant for rental prices. Consequently, German farmland rental rates are heavily influenced by agricultural policy instruments and therefore, these policies exhibit substantial distributional effects.
Keywords: Q15; Q18; H22; 330; farmland rental price; per-hectare payment; spatial econometrics; subsidy incidence